Inactivated vaccines derived from bovine viral diarrhea virus B3 strain elicit robust and specific humoral and cellular immune responses - Xu, Ming-Guo; Wu, Ao-Di; Liu, Jing-Nan; Yang, Zhong-Lian; Li, Hong-Huan; Ma, Hai-Long; Yang, Ning-Ning; Sheng, Jin-Liang; Chen, Chuang-Fu (Frontiers in Microbiology, 2025)
IntroductionBovine viral diarrhea-mucosal disease (BVD-MD) is a significant viral disease in cattle caused by infection with bovine viral diarrhea virus (BVDV). Xinjiang, a major pastoral region in China, is heavily affected by this disease. Owing to the high genetic variability of BVDV, developing cross-protection vaccines targeting predominant strains is essential.MethodsIn this study, inactivated vaccines were developed using BVDV strains isolated from Xinjiang, including BVDV-1 (B1), BVDV-2 (B2), XJ-BVDV-3 (B3), and BVDV-LC (LC). BALB/c mice were immunized, and immune responses were assessed via ELISpot, ELISA, and virus neutralization assays. On day 42 post-immunization, the mice were challenged with BVDV, and the viral loads were quantified.ResultsThe vaccines showed stable characteristics and sterility and are suitable for immunization studies. All the vaccines stimulated interferon-gamma (IFN-γ) production, and the IFN-γ levels in the B1 and B3 groups were significantly higher than those in the commercial vaccine group (p < 0.0001). The ELISA results revealed specific IgG, IgG1, and IgG2a antibodies. Neutralization assays revealed that the B3- and LC-inactivated vaccine groups presented significantly higher neutralizing antibody titers than did the commercial vaccine group ((p < 0.05). Tissue viral load detection revealed that the inactivated vaccines reduced the viral load across various tissues.DiscussionIn conclusion, this study developed inactivated vaccines from the B1, B2, B3, and LC strains, all of which induce robust immune responses. Among these, the B3 inactivated vaccine show great potential for commercialization, providing a valuable reference for BVDV prevention and control in Xinjiang.